Safety and efficacy of plasmapheresis in treatment of acute fatty liver of pregnancy—a systematic review and meta-analysis - Siwatch, Sujata; De, Arka; Kaur, Bandhanjot; Lamba, Divjot Singh; Kaur, Simarpreet; Singh, Virendra; Periyasamy, Aravind Gandhi (Frontiers in Medicine, 2024)
Introduction Acute fatty liver of pregnancy (AFLP) is a fatal disease occurring in 3rd trimester. The safety and efficacy of plasmapheresis/plasma exchange (PP/PE) as an adjunctive treatment in patients of AFLP has been studied. We performed systematic review and meta-analysis to estimate the clinical parameters that included mortality rates and improvement of the biochemical parameters including Liver and Renal function enzymes, coagulopathy factors of AFLP patients. Methods We searched PubMed, Ovid MEDLINE, Cochrane, CINAHL and Scopus, ClinicalTrials.gov. RevMan statistical software was used for meta-analysis. Results Pooled survival proportion for AFLP patients treated with PP/PE was 87.74% (95% CI: 82.84 to 91.65). Efficacy of PP/PE was studied by its effect on mortality. PE/PP was associated with the reduction in the mortality with pooled odds ratio of 0.51 (95% CI: 0.08 to 3.09) with I2 = 86%. Sensitivity analysis after excluding outlier study, yielded a pooled odds ratio of 0.19 (95% CI: 0.02 to 1.52) with reduced heterogeneity (I2 = 63%). Biochemical parameter analysis demonstrated significant improvement post-PP/PE treatment, including decreased bilirubin (MD: 8.30, 95% CI: 6.75 to 9.84), AST (MD: 107.25, 95% CI: 52.45 to 162.06), ALT (MD: 111.08, 95% CI: 27.18 to 194.97), creatinine (MD: 1.66, 95% CI: 1.39 to 1.93), and Prothrombin time (MD: 5.08, 95% CI: 2.93 to 7.22). Discussion Despite some heterogeneity, PP/PE shows promise in improving biochemical parameters in AFLP patients. PE can serve as a therapeutic approach for AFLP particularly in severe or refractory cases. PE provides the time for organ to recover and helps in creating a homeostatic environment for liver. Large RCTs and propensity matched studies are needed to better understand the safety and efficacy of the treatment. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022315698.